Chlorophylls - Ameen, Sadia; Shaheer Akhtar, M.; Shin, Hyung-Shik (IntechOpen, 2022)
Chlorophyll, a green pigment present in almost all plants, algae, and cyanobacteria, is a significant biomolecule essential to photosynthesis, the process by which plants convert light into energy. This book provides a comprehensive and easy-to-understand source of information on the latest developments in chlorophyll research. It is a collection of contributions from leading specialists in the subject. Topics discussed include the medicinal uses of chlorophyll, the electronic structure of chlorophyll monomers and oligomers, and chlorophyll estimate from fluorescence vertical profiles in the ocean.